Multi-Objective Optimization By Ratio Analysis (MOORA) Sebagai Implementasi Rekomendasi Penghargaan Dosen Berbasis Website - Iksan, Helmi; Wibowo, Setyoningsih; Handayanto, Agung (Jurusan Informatika STTR Cepu, 2024)
Lecturers are professional educators and scientists with the main task of transforming, developing and disseminating science, technology and art through education, research and community service. Based on Republic of Indonesia Government Regulation Number 37 of 2009 concerning lecturers. Article 19 paragraph 1 states that lecturers who carry out their professional duties are entitled to receive awards. This shows that determining the right choice of award is very important for lecturers as an appreciation for their performance, so it is necessary to discuss and create a Decision Support System using the Multi-Objective Optimization by Ratio Analysis (MOORA) method as an implementation of recommendations for lecturer awards based on research and service performance. website-based community with the data used is data from lecturers from the Informatics Study Program, Faculty of Engineering and Informatics, taken from PGRI University Semarang. In building a Decision Support System application, the Waterfall method is used. For system modeling using Unified Modeling Language (UML), the software used to build this system uses the Hypertext Preprocessor (PHP) and XAMPP programming language as a connection to the database, namely MySQL. System testing uses User Acceptance Testing (UAT), black box and white box methods. With this lecturer reward system, it is hoped that it can encourage lecturers to achieve positively and be more productive.